PROSPECÇÃO DO SISTEMA ECONÔMICO E INCORPORAÇÃO DA ESTRATÉGIA DA INOVAÇÃO PARA O DESENVOLVIMENTO TERRITORIAL: O CASO DO MUNICÍPIO DE LUZERNA-SC - SARAIVA, ILLYUSHIN ZAAK (2020)
The 4th Industrial Revolution articulated technical means and productive forces at a level never seen before in the history of capitalism, increasing competition and differentiation between central and dependent countries in the technological field. The literature demands to identify industrial clusters, composing information to elaborate public policies to support local production systems. This work has as main objective to prospect the Economic System of Luzerna City, Brazil, allowing the incorporation of the Innovation Strategy for the territorial development, and formulation of medium and long term policies. The research was exploratory and descriptive, and the data collection was documentary, based on socioeconomic data published by bodies such as IBGE, IPEA, CNI, FIESC, BNDES, World Bank, and data from the City Hall. The master's products were 11 articles published by the author, highlighting as the main results of the research that the Industrial Electrometalmechanical Concentration of Luzerna is the largest in the State of Santa Catarina, in addition to the high degree of innovation in its trade balance, exporting only finished products manufacturing, and although highly industrialized, the municipality is able to produce in its territory a significant part of the parts and materials currently imported, increasing the degree of innovation of the products generated over those consumed, adding value in the territory and generating sustainable development.